Szabadidő-lakások az Alföldön - Csordás, László (Tér és Társadalom, 1993)
The bungalow, summer holiday home, weekend house, or whatever we call it, are among the second homes used in leisure time, for leisure time purposes. The study deals with the second homes (a building that is a private property or a long term rental, and that serves as a temporary accommodation for a family that lives elsewhere, it has not only leisure time functions, but also training and occupational ones) and the leisure time homes (all "other homes" of a person, that, besides the main home, is used mainly in the leisure time and temporarily: on weekdays after work, on the weekends or during the holiday. An object can be called "other home" if it is owned by the user, or it can be used for at least two succeeding months based on a lease contract). After the introduction of their foreign definitions and explaining the general reasons for the development of leisure time homes, it details the most important features of the holiday settlements, holiday homes, and holiday home owners at Great Plain, county and settlement levels. The most important statements of the study are the following briefly: 1) In 102 settlements of the Great Plain there were 19,654 holiday homes registered by the tax office (TAKEH), while in 168 settlements only 11,889 were registered by the Land Office. 2) The holiday homes and weekend houses used for holiday purposes, developed along riverbanks, shores of lakes, around thermal spas and in fenced gardens (Map 1.). 3) The weekend houses in the Great Plain built between 1970-1992 are mainly in the Southern counties of the Great Plain, though the peak rate of building holiday homes pushed from the South to the North in time Fig. 1.). 4) 73.9% of all the owners live in Great Plain counties. In every county most of the holiday home owners are from within the county population. The rate of the owners from the same county is 68.0%, if we look at the whole of the Great Plain. The rate of those who own holiday homes in their own counties increases in a direct proportion with the distance from the main, extra-regional attraction centres (Budapest, Northern Hungary; the rates of Csongrád county is 93.8%, while that of Békés is 88.4%), while the same rate decreases to 55.4% in Bács-Kiskun, 45.5% in Szolnok county because of the closeness of the capital. 10.4% of the Great Plain’s holiday homes are owned by Budapest citizens, though this is different in the counties: hardly 1.1 % and 1.2% in the far-away Csongrád and Szabolcs-Szatmár counties, while 18.1% in Szolnok and 20.9% in Bács-Kiskun county. 5) Most of the owners live in the big cities (Table 1.1% of the settlements (county seats and the capital) give almost 57% of the owners, while just above 8% live in 80% of the settlements. 6) The holiday home owners of the six Great Plain counties are 699 Hungarian, 1 German and 1 Swedish settlement (Map 2). We can see (Table 2.) that the average number of Great Plain holiday home owners per settlements, varies according to the population categories: 2,044 in the capital, 978 in the major cities, 155 in towns with population between 50,000-100,000, 77 in towns with 20,000-50,000 dwellers, and 30 holiday home owners can be found in the settlements of 10,000-20,000 citizens. In rural settlements the number of holiday home owners is 1-10 on the average. While 50.23% of the owners live in settlements with populations bigger than 100,000 (9 settlements altogether), only 22.3% in the 483 settlements with populations between 1,000-10,000. Ön the other hand, the number of Great Plain holiday home owners per thousand residents does not vary in such a significant way among the population size categories. 7) Almost one-fourth of the holiday homes of the six Great Plain counties can be found in five county seats (Békéscsaba has no holiday homes), but 46.54% of the owners of the almost 20,000 holiday homes live there. 93.9-98.4% of the owners of weekend houses (or, many times, "midweek, everyday houses") of the county seats are local residents. So we can see that just a little more than half of the existing holiday needs (at Great Plain level) can be satisfied in the county seats. 8) 87 –97% of the county seats’ resident holiday home owners have holiday homes in their own counties (Table 3.). Out of the 4,794 holiday homes of the Great Plain county seats, the owners of 4,640 live in the given county seat (Table 4.). The rate of the owners who are Szeged and Debrecen residents is significant, in their county seats, in their counties (above 65%), while the Kecskemét residents show a figure of "only" 17% (Table 5.). 9) From the years of birth of the taxpayers we can say that most of the owners are either aged (28.6 of them are older than 60) or of older active age 53.6% of them are between 41-60), thus the generation that does not have to deal with rearing their children, is in the consolidation phase of the life cycle, many times ill etc. 10) The area subject to taxation of the holiday homes is 31.3 m2 . Since the law did not allow the construction of holiday homes bigger than 30 m 2in fened gardens, I examined the rate of the buildings of 30 m2 or less. We can say that 56.8% of the Great Plain summer homes have areas, of 30 m2 or less. But in Csongrád and Hajdú-Bihar more than 70% of the buildings fali into this category. 39% is the rate of the mediumsize (31-59 m2) holiday homes, but less than 26% in the above-mentioned two counties. The rate of the buildings of 60 m2 or more Was insignificant in 1989 (4.2%), though in the counties that can be characterised by the expansion of leisure time areas (Szolnok, Szabolcs-Szatmár) their rate is up to 5.6-6.6%. In more than one-third of the 102 settlements that have holiday homes the rate of those buildings that are smaller than 30 m2 is above 75%, and it is only along the Tisza river where it is under 25%.